2023
DOI: 10.1097/tp.0000000000004559
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to mTOR Inhibitor to Reduce the Incidence of Cytomegalovirus Recurrence in Kidney Transplant Recipients Receiving Preemptive Treatment: A Prospective, Randomized Trial

Abstract: Background. Although mammalian target of rapamycin inhibitors (mTORi) are associated with a lower incidence of the first episode of cytomegalovirus (CMV) infection/disease in kidney transplant recipients receiving calcineurin inhibitors (CNIs), the efficacy and safety of the conversion from the antimetabolite to an mTORi for the prevention of CMV recurrence are unknown. Methods. In this single-center prospective randomized trial, low-immunological-risk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In a recent single-center prospective randomized trial conducted by Viana et al with a 12-month follow-up, 72 kidney-transplant recipients who had undergone treatment for a first episode of CMV infection/disease either were maintained on the same treatment (antiproliferative agent plus CNIs) or had the antiproliferative replaced with sirolimus. The study found that CMV recurrence occurred in 43% of patients in the control group, whereas the sirolimus group had no recurrence (p ≤ 0.0001) [85]. In de novo kidney-transplant recipients, avoiding CMV infection/disease can be achieved to some extent by replacing the antiproliferative agent (mycophenolic acid) with everolimus [19,86].…”
Section: Viral Reactivationmentioning
confidence: 99%
“…In a recent single-center prospective randomized trial conducted by Viana et al with a 12-month follow-up, 72 kidney-transplant recipients who had undergone treatment for a first episode of CMV infection/disease either were maintained on the same treatment (antiproliferative agent plus CNIs) or had the antiproliferative replaced with sirolimus. The study found that CMV recurrence occurred in 43% of patients in the control group, whereas the sirolimus group had no recurrence (p ≤ 0.0001) [85]. In de novo kidney-transplant recipients, avoiding CMV infection/disease can be achieved to some extent by replacing the antiproliferative agent (mycophenolic acid) with everolimus [19,86].…”
Section: Viral Reactivationmentioning
confidence: 99%
“…Despite preclinical experiments confirming the role of mTOR inhibitors in a variety of diseases, most clinical trials focus on their application in organ transplant as a potent immunosuppressant. In terms of graft-versus-host disease (GVHD) prophylaxis, the addition of sirolimus to standard therapy is propitious to reducing the incidence and severity of graft-versus-host disease (GVHD) and improving the life quality in kidney transplant recipients ( 241 , 242 , 254 , 255 ). Additionally, everolimus improves the prognosis of liver or heart transplants with fewer adverse effects ( 256 , 257 ).…”
Section: Therapeutic Implications Of Mtor Inhibitors In Clinical Trialsmentioning
confidence: 99%
“…In the current issue of Transplantation , Viana et al 7 demonstrate that the conversion from an antimetabolite to mTORi after the treatment of the first episode of CMV was effective in preventing recurrent episodes of CMV in CMV-seropositive KTRs. In this single-center, prospective trial, all adult CMV-positive KTRs who developed the first episode of CMV infection or disease within the first 6 mo after transplantation were randomized to be converted to sirolimus (SRL) or not (control group) immediately after the treatment of the CMV event.…”
mentioning
confidence: 97%